Asphalt-based amorphous carbon negative electrode of sodium-ion battery, preparation method of asphalt-based amorphous carbon negative electrode and sodium-ion battery
By heating the asphalt powder and stirring a high-concentration acid solution, a tight three-dimensional network structure is formed and high-temperature carbonization is carried out in the protective atmosphere, the problem of uneven oxidation of asphalt-based carbon materials in the prior art is solved, and excellent electrochemical performance and simple preparation process are achieved.
Patent Information
- Application Number
- CN202510360350.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-06-24
AI Technical Summary
The existing asphalt-based carbon materials cannot be oxidized quickly and uniformly in traditional oxidation methods, resulting in poor rate performance and cyclic performance, complex preparation process and high cost, limiting their large-scale commercial application.
By heating the asphalt powder, it changes from hydrophobicity to hydrophilicity, and then stirred in a high-concentration acid solution to form a tight three-dimensional network structure, and then high-temperature carbonization is carried out in a protective atmosphere to inhibit the melt rearrangement process of carbon atoms, reduce the degree of graphitization and introduce a hard carbon disordered carbon structure.
It has achieved excellent electrochemical performance of asphalt-based carbon materials, excellent rate performance, slow capacity attenuation, simple operation and excellent yield, and is suitable for large-scale commercial applications.
Smart Images

Figure CN120191919A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and particularly to a sodium-ion battery pitch-based amorphous carbon negative electrode and a preparation method thereof, and a sodium-ion battery. Background Art
[0002] With the continuous development of the scientific and technological society, energy crises and environmental pollution problems have emerged. Various renewable energy technologies are restricted by time and space and cannot output stably and continuously. Therefore, it is particularly important to find a safe and stable electrochemical energy storage technology. Among them, lithium-ion batteries stand out among many electrochemical energy storage technologies. However, lithium-ion batteries also have various disadvantages, such as the shortage and uneven distribution of lithium resources, low safety, high cost, etc. Therefore, finding a new type of ion battery that can replace lithium-ion batteries with both economy and safety has become a major research focus.
[0003] Sodium-ion batteries have the advantages of rich sodium resources, low cost, high safety, etc., and do not use precious metals such as lithium and cobalt. Therefore, sodium-ion batteries are expected to replace lithium-ion batteries, especially in the field of large-scale fixed energy storage devices. When studying the negative electrode materials of sodium-ion batteries, people first thought of applying the successful experience of graphite in lithium-ion batteries to sodium-ion batteries. However, due to thermodynamic instability, sodium ions and graphite negative electrodes cannot form stable first-order intercalation compounds. Therefore, people turned their attention to other carbon materials, and pitch-based carbon materials have been widely studied because of their low cost and rich raw material sources.
[0004] However, the preparation processes of most current pitch-based carbon negative electrode materials are complex and require the introduction of oxygen for pretreatment, which will increase the preparation cost and is not conducive to large-scale commercial applications.
[0005] It should be noted that the information disclosed in the above background art section is only used for understanding the background of the present application, and therefore may include information that does not constitute the prior art known to those of ordinary skill in the art. Summary of the Invention
[0006] In order to make up for the deficiencies of the prior art, the present invention provides a sodium-ion battery pitch-based amorphous carbon negative electrode and a preparation method thereof, and a sodium-ion battery.
[0007] The present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing an asphalt-based amorphous carbon negative electrode for a sodium-ion battery, comprising the following steps: (1) heating asphalt powder in air and then cooling it to room temperature; (2) grinding the material processed in step (1) into powder, adding it to a concentrated acid solution, and stirring at room temperature for 5 min ≤ stirring time < 20 min; (3) washing the reaction solution processed in step (2) with water until pH = 7, filtering, drying the obtained filter cake, and grinding it into powder at room temperature; (4) heating the powder obtained in step (3) from room temperature to 1200 - 1400 °C in a protective atmosphere, holding for 0.5 - 2.5 h, and then cooling to room temperature; (5) collecting the material processed in step (4) at room temperature and grinding it into powder to obtain the product.
[0009] Further, in step (1), after putting the asphalt powder into a graphite crucible, it is placed in a muffle furnace and heated from room temperature to 300 - 400 °C, held at 300 - 400 °C for no more than 2 h, and then cooled to room temperature in the furnace; in step (4), after putting the powder obtained in step (3) into a graphite crucible, it is placed in a high-temperature tube furnace for heating and holding, and then cooled to room temperature in the furnace.
[0010] Further, in the concentrated acid solution of step (2), the concentration of the acid is 10 - 30 wt%; preferably, the concentrated acid is at least one of concentrated nitric acid, concentrated sulfuric acid, and concentrated hydrochloric acid.
[0011] Further, in step (2), at least 50 ml of concentrated acid solution is added per 1 g of powder.
[0012] Further, in step (4), the protective atmosphere is at least one of argon, nitrogen, helium, neon, and xenon.
[0013] Further, in step (1), the heating rate is 5 °C / min and no additional gas is passed.
[0014] Further, in step (4), when heating from room temperature to 1000 °C, the heating rate is 5 °C / min, and when heating from 1000 °C to 1200 - 1400 °C, the heating rate is 1 - 2 °C / min.
[0015] Further, in step (3), the reaction solution processed in step (2) is first centrifuged in a refrigerated centrifuge, the lower precipitate after centrifugation is collected, and then washed with water until pH = 7.
[0016] In a second aspect, the present invention also provides an asphalt-based amorphous carbon negative electrode for a sodium-ion battery, which is prepared by the preparation method described in the first aspect.
[0017] In a third aspect, the present invention also provides a sodium-ion battery, comprising the asphalt-based amorphous carbon negative electrode for a sodium-ion battery described in the second aspect.
[0018] The present invention has the following beneficial effects:
[0019] The preparation method of the present invention can solve the problems that the asphalt-based carbon material cannot be rapidly and uniformly oxidized in the traditional oxidation method, and the rate performance and cycle performance of the prepared asphalt-based carbon material are not good. Specifically, the present invention first heats the asphalt powder to make it change from hydrophobic to hydrophilic, and then uses a high-concentration acid solution as a treatment agent to form a relatively compact three-dimensional network structure before the high-temperature carbonization of the material, thereby inhibiting the melting and rearrangement process of carbon atoms in the subsequent high-temperature carbonization process, reducing the graphitization degree of the asphalt-based carbon material, introducing more hard carbon disordered carbon structures into the soft carbon ordered graphite structure, and making the product have excellent electrochemical properties (excellent rate performance and slow capacity decay rate).
[0020] The preparation means provided by the present invention is simple in operation, excellent in yield, and the synthesized asphalt-based amorphous carbon negative electrode material has relatively excellent electrochemical properties. Brief Description of the Drawings
[0021] Figure 1a It is a high-resolution transmission electron microscope (HRTEM) image of the asphalt-based amorphous carbon negative electrode material obtained in Example 1 of the present invention.
[0022] Figure 1b and 1c They are SEM images of the asphalt-based amorphous carbon negative electrode material obtained in Example 1 of the present invention at different magnifications.
[0023] Figure 1d It is an SEM image of the material obtained in Comparative Example 1.
[0024] Figure 2a It is an XRD diagram of the materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0025] Figure 2b - Figure 2d They are diagrams showing the calculation of the R value from the XRD diagrams of the materials obtained in Comparative Example 2, Example 1 and Comparative Example 1 respectively. Figure 3 It is the rate performance of the current test of the asphalt-based amorphous carbon negative electrode material obtained in Example 1 of the present invention.
[0026] Figure 4a and 4b They are the electrochemical charge-discharge curves of Example 1 and Comparative Example 1 respectively. Detailed Embodiments
[0027] The following makes a detailed description of the embodiments of the present invention. It should be emphasized that the following description is merely exemplary and not intended to limit the scope of the present invention and its applications.
[0028] In this article, "room temperature" refers to a temperature in the range of 25-30 °C.
[0029] The specific implementation mode of the present invention provides a preparation method for an asphalt-based amorphous carbon anode of a sodium-ion battery, including the following steps:
[0030] (1) Heat the asphalt powder in air and then cool it to room temperature to introduce hydroxyl groups on the surface of the asphalt, changing the asphalt powder from hydrophobic to hydrophilic;
[0031] (2) Grind the material processed in step (1) (at this time, the asphalt powder aggregates into a block) into powder, add it to a concentrated acid solution, and stir at room temperature for 5 min ≤ stirring time < 20 min;
[0032] (3) Wash the reaction solution processed in step (2) with water until the pH = 7, filter, dry the obtained filter cake, and grind it into powder at room temperature;
[0033] (4) Heat the powder obtained in step (3) from room temperature to 1200 - 1400 °C in a protective atmosphere, keep it warm for 0.5 - 2.5 h, and then cool it to room temperature; during this high-temperature carbonization process, the material forms an ordered-disordered mixed carbon structure
[0034] (5) Collect the material processed in step (4) at room temperature and grind it into powder to obtain the product.
[0035] In some embodiments, in step (1), after putting the asphalt powder into a graphite crucible, place it in a muffle furnace and heat it from room temperature to 300 - 400 °C, keep it warm at 300 - 400 °C for no more than 2 h, and then cool the furnace to room temperature; in step (4), after putting the powder obtained in step (3) into a graphite crucible, place it in a high-temperature tube furnace for heating and insulation, and then cool the furnace to room temperature.
[0036] In some embodiments, in the concentrated acid solution of step (2), the concentration of the acid is 10 wt%.
[0037] In some embodiments, the stirring time in step (2) is 10 min.
[0038] In some embodiments, the concentrated acid is at least one of concentrated nitric acid, concentrated sulfuric acid, and concentrated hydrochloric acid.
[0039] In some embodiments, in step (2), at least 50 ml of concentrated acid solution is added for every 1 g of powder.
[0040] In some embodiments, in step (4), the protective atmosphere is at least one of argon, nitrogen, helium, neon, and xenon.
[0041] In some embodiments, in step (1), the heating rate is 5 °C / min, and no additional gas is introduced (i.e., the asphalt powder is heated under the air existing in the muffle furnace itself).
[0042] In some embodiments, in step (4), when heating from room temperature to 1000 °C, the heating rate is 5 °C / min, and when heating from 1000 °C to 1200 - 1400 °C, the heating rate is 1 - 2 °C / min. By heating rapidly first and then slowly, the reaction temperature can be reached, and the heating can be more uniform, forming a more uniform and better-performing material.
[0043] In some embodiments, in step (3), the reaction solution after being treated in step (2) is first centrifuged in a refrigerated centrifuge. After collecting the lower-layer precipitate after centrifugation, it is then washed with water until the pH = 7.
[0044] In some preferred embodiments, a method for preparing a sodium-ion battery asphalt-based amorphous carbon negative electrode includes the following steps:
[0045] (1) The asphalt powder is heated in air at 300 - 400 °C and then cooled to room temperature.
[0046] (2) The material after being treated in step (1) is ground into powder, added to a concentrated nitric acid solution with a concentration of 10 wt%, and stirred at room temperature for 10 min.
[0047] (3) The reaction solution after being treated in step (2) is centrifuged, and after collecting the lower-layer precipitate after centrifugation, it is washed with water until the pH = 7, filtered, and the obtained filter cake is dried and ground into powder at room temperature.
[0048] (4) The powder obtained in step (3) is heated from room temperature to 1200 - 1400 °C in a protective atmosphere, held for 0.5 - 2.5 h, and then cooled to room temperature.
[0049] (5) The material after being treated in step (4) is collected at room temperature and ground into powder to obtain the product.
[0050] The specific embodiment of the present invention further provides a sodium-ion battery asphalt-based amorphous carbon negative electrode, which is prepared by the above preparation method.
[0051] The specific embodiment of the present invention further provides a sodium-ion battery, including the sodium-ion battery asphalt-based amorphous carbon negative electrode.
[0052] The following further describes the specific embodiments of the present invention.
[0053] Example 1
[0054] The method for preparing a sodium-ion battery asphalt-based amorphous carbon negative electrode includes the following steps:
[0055] (1) Put the asphalt powder into a graphite crucible and then place it in a muffle furnace. Heat it from room temperature to 300 °C at a heating rate of 5 °C / min, keep it at 300 °C for 2 h, and then cool it to room temperature in the furnace;
[0056] (2) Grind the material treated in step (1) into powder, add it to a concentrated nitric acid aqueous solution with a nitric acid concentration of 10 wt%, 1 g of the material corresponds to 50 ml of the concentrated nitric acid aqueous solution, and stir at room temperature for 10 min;
[0057] (3) Centrifuge the reaction solution treated in step (2) in a refrigerated centrifuge first, collect the lower-layer precipitate after centrifugation, wash the lower-layer precipitate with deionized water until the pH = 7, filter, and dry the obtained filter cake in an 80 °C oven overnight until dry, and grind it into powder at room temperature;
[0058] (4) Put the powder obtained in step (3) into a graphite crucible and then place it in a high-temperature tube furnace. Under the protection of argon, heat it from room temperature to 1000 °C at a heating rate of 5 °C / min, then heat it from 1000 °C to 1400 °C at a heating rate of 1 °C / min, then keep it at a temperature for 2 h, and then cool it to room temperature in the furnace;
[0059] (5) Collect the material treated in step (4) at room temperature and grind it into powder to obtain the product (i.e., the sodium-ion battery asphalt-based amorphous carbon negative electrode).
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the stirring time at room temperature in step (2) is 20 min, and the other steps are the same as those in Example 1.
[0062] Comparative Example 2
[0063] The difference from Example 1 is that it does not include the concentrated nitric acid treatment in step (2), and the other steps are the same as those in Example 1.
[0064] As Figure 1a shown, it is the high-resolution transmission electron microscope (HRTEM) image of the asphalt-based amorphous carbon negative electrode material obtained in Example 1 of the present invention. As Figure 1b and 1c shown, the asphalt-based amorphous carbon negative electrode material with regular morphology is obtained in Example 1 of the present invention. The particle size is in the micron scale, and the particle diameter is in the range of 3 - 5 μm. There is only a small amount of agglomeration phenomenon, showing blocky particles. As Figure 1d shown, it is the SEM image of the material obtained in Comparative Example 1. It can be seen from this that there is a relatively obvious agglomeration phenomenon in Comparative Example 1.
[0065] As Figure 2aThe XRD patterns of the materials obtained in Example 1 of the present invention (represented by the curve marked "10 minutes" in the figure), Comparative Example 1 (represented by the curve marked "20 minutes" in the figure), and Comparative Example 2 (represented by the curve marked "0 minutes" in the figure) are shown as follows. Figure 2b - Figure 2d The following are the diagrams showing the calculation of the R value from the XRD patterns of the materials obtained in Comparative Example 2, Example 1, and Comparative Example 1 respectively. After calculation, the R values are shown in Table 1 below:
[0066] sample B value A value R value (= B / A) Comparative Example 1 5480 2214 2.47 Example 1 6340 2434 2.60 Comparative Example 2 5073 1680 3.02
[0067] The smaller the R value, the higher the degree of disorder of the material. The R value of Example 1 is 2.60, which is a relatively good degree of disorder value.
[0068] The process of testing the electrochemical performance of the products obtained in the examples and comparative examples of the present invention is as follows:
[0069] The product obtained in Example 1 above, conductive agent Super P, and binder CMC were mixed into a slurry in a mass ratio of 8:1:1, and then coated on a copper foil current collector with a controlled thickness. Using 1 mol / L NaPF6 in DEGDME as the electrolyte, a Na sheet as the negative electrode, and a layer of glass fiber filter paper diaphragm GFA as the diaphragm, a button cell was assembled in a glove box filled with argon. Then, the charge-discharge capacity and rate performance were tested on a Land CT2001A battery test system produced by Wuhan Jinnuo Electronics Co., Ltd. Similarly, the product obtained in Comparative Example 1 above was assembled into a button cell in the same manner.
[0070] As Figure 3 shown, after cycling five times at currents of 30 mA / g, 100 mA / g, 300 mA / g, 500 mA / g, 1000 mA / g, and 2000 mA / g respectively, and then cycling 70 times at a current of 100 mA / g to test its rate performance, it can be seen that this method can provide a high initial discharge capacity and has relatively good rate performance. After the current returns to 100 mA / g, it can still cycle stably.
[0071] As Figure 4a and 4b shown, they are the electrochemical charge-discharge curves of Example 1 and Comparative Example 1 respectively, indicating that the capacity decay rate of Example 1 of the present invention is slower.
[0072] In the above embodiments, the asphalt powder is first pretreated in a muffle furnace and then stirred in a concentrated nitric acid solution (high-concentration nitric acid is used as a treatment agent to form a relatively compact three-dimensional network structure before the material is carbonized at high temperature, thereby inhibiting the melting and rearrangement process of carbon atoms during the subsequent high-temperature carbonization process, reducing the graphitization degree of the asphalt-based carbon material, and introducing more hard carbon disordered carbon structures into the soft carbon ordered graphite structure). After the stirring reaction, it is washed with deionized water and dried in a vacuum oven. The dried material is then carbonized at high temperature in a high-temperature tube furnace, and the material is collected at room temperature. The preparation method is simple and the yield is excellent, which is 63% (the yield of the material obtained in Comparative Example 2 before treatment is 54%). The particle size of the synthesized asphalt-based carbon negative electrode material is in the range of 3-5 μm. It has an ordered and disordered mixed carbon structure and excellent electrochemical performance.
[0073] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is only limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, they can make several substitutions or modifications to these described embodiments, and these substitution or modification methods should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description with reference to terms such as "one embodiment", "some embodiments", "preferred embodiment", "example", "specific example", or "some examples" means that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples. Without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions, and alterations can be made herein without departing from the scope of protection of the patent application.
Claims
1. A method for preparing a sodium ion battery asphalt-based amorphous carbon negative electrode, characterized in that: The steps include: (1) heating the asphalt powder in air and then cooling it to room temperature; (2) Grinding the material treated in step (1) into powder, adding it to a concentrated acid solution, stirring at room temperature, and stirring time of 5 min≤<20 min; (3) washing the reaction solution treated in step (2) with water until the pH value is 7, filtering, drying the obtained filter cake, and grinding it into powder at room temperature; (4) heating the powder obtained in step (3) from room temperature to 1200-1400° C. in a protective atmosphere, keeping the temperature for 0.5-2.5 h, and then cooling to room temperature; (5) Collecting the material treated in step (4) at room temperature, grinding it into powder to obtain a product.
2. The preparation method according to claim 1, characterized in that In step (1), the asphalt powder is placed in a graphite crucible, and then placed in a muffle furnace and heated from room temperature to 300-400° C., and then kept at 300-400° C. for no more than 2 h, and then cooled to room temperature; In step (4), the powder obtained in step (3) is placed in a graphite crucible, and then placed in a high-temperature tubular furnace for heating and heat preservation, and then the furnace is cooled to room temperature.
3. The preparation method according to claim 1, characterized in that: In the concentrated acid solution of step (2), the acid concentration is 10-30wt%; preferably, the concentrated acid is at least one of concentrated nitric acid, concentrated sulfuric acid and concentrated hydrochloric acid.
4. The preparation method according to claim 1, characterized in that: In step (2), at least 50 ml of concentrated acid solution is added for every 1 g of powder.
5. The preparation method according to claim 1, characterized in that: In step (4), the protective atmosphere is at least one of argon, nitrogen, helium, neon and xenon.
6. The preparation method according to claim 2, characterized in that: In step (1), the heating rate is 5°C / min, and no additional gas is passed.
7. The preparation method according to claim 1, characterized in that: In step (4), when the temperature is increased from room temperature to 1000°C, the heating rate is 5°C / min, and when the temperature is increased from 1000°C to 1200-1400°C, the heating rate is 1-2°C / min.
8. The preparation method according to claim 1, characterized in that: In step (3), the reaction solution treated in step (2) is first centrifuged in a refrigerated centrifuge, and the lower sediment after centrifugation is collected and then washed with water until the pH value is 7.
9. A sodium ion battery asphalt-based amorphous carbon negative electrode, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: It includes the asphalt-based amorphous carbon negative electrode for a sodium ion battery as described in claim 9.